Adolescents' Motivations to Engage in Social Distancing During the COVID-19 Pandemic: Associations With Mental and Social Health - Oosterhoff, Benjamin; Palmer, Cara A.; Wilson, Jenna; Shook, Natalie (Journal of adolescent health, 2020)
Reducing the spread of infection during the COVID-19 pandemic prompted recommendations for individuals to socially distance. Little is known about the extent to which youth are socially distancing, what motivations underlie their social distancing, and how these motivations are connected with amount of social distancing, mental health, and social health. Using a large sample of adolescents from across the United States, this study examined adolescents' motivations for social distancing, their engagement in social distancing, and their mental and social health. Data were collected on March 29th and 30th, 2020, two weeks after COVID-19 was declared a national emergency in the United States. The sample consisted of 683 adolescents recruited using social media. A series of multiple linear regressions examined unique associations among adolescents' motivations to engage in social distancing, perceived amount of social distancing, anxiety symptoms, depressive symptoms, burdensomeness, and belongingness. Almost all respondents (98.1%) reported engaging in at least a little social distancing. The most commonly reported motivations for social distancing concerned social responsibility and not wanting others to get sick. Motivations concerning state or city lockdowns, parental rules, and social responsibility were associated with greater social distancing, whereas motivations concerning no alternatives were associated with less social distancing. Specific motivations for social distancing were differentially associated with adolescents' anxiety symptoms, depressive symptoms, burdensomeness, and belongingness. Understanding adolescents' motivations to engage in social distancing may inform strategies to increase social distancing engagement, reduce pathogen transmission, and identify individual differences in mental and social health during the COVID-19 pandemic.